Redescription, new records and host plant for Sysinas centralis Distant, (Hemiptera: Heteroptera: Miridae) - Ferreira, Paulo Sérgio Fiuza; Costa, Luiz Ant]Nio Alves; Coelho, Lívia Aguiar (Zootaxa, 2007)
The Neotropical bryocorine plant bug, Sysinas centralis Distant, is reported for the first time in Central America, based in one male specimen collected in Guatemala. Additional new records include Cuba, Jamaica, and Brazil. A redescription of adults, figures of habitus, male and female genitalia, color pattern variations, geographic distribution, and a new host plant are provided. Diagnostic characters are provided to distinguish this species from others in the same genus.